Computational Simulation of Abrasive Flow Machining For Two Dimensional Models. (2018) - Pal, Pawan; Jain, K.K.
Abstract: Advancement of surface finish and material removal has been quite a difficult task in a finishing operation such as abrasive flow machining (AFM). Factors that affect the surface finish and metal removal are media viscosity, piston velocity, extrusion pressure, and particle size in abrasive flow machining process. Performing experiments for all the parameters of AFM and precisely getting an improved parameter in a short time are difficult to accomplish because the operation requires a precise finish. Computational fluid dynamics (CFD) simulation was employed to accurately determine optimum parameters. In the present work, a two dimensional model was designed, and compared with the available experimental data. the flow analysis, force calculation, are studied at different volume fraction were performed. A CFD simulation was performed by using commercially available ANSYS FLUENT. The fluid was taken as a Newtonian fluid and the flow laminar with no wall slip and multiphase mixture model was taken into account two phases were selected for the flow analysis.